Molecular mechanisms of diabetic retinopathy, general preventive strategies and novel therapeutic targets - Safi, S.Z.; Qvist, R.; Kumar, S.; Ismail, I.S.B. (2013)
The growing number of people with diabetes worldwide suggests that DR and DME will continue to be sight threatening factors. The pathogenesis of diabetic retinopathy is a widespread cause of visual impairment in the world and a range of hyperglycemia-linked pathways have been implicated in the initiation and progression of this condition. Despite understanding the polyol pathway flux, activation of protein kinase C (KPC) isoforms, Igf-I signaling in response to hyperglycemia, increased hexosamine pathway plux and increased advanced glycation end-product (AGE) formation, pathogenic mechanisms underlying diabetes induced vision loss are not fully understood. More than 50 years of its introduction, destruction of damaged retina by photocoagulation remains the primary treatment among the physicians. Scatter or panretinal laser photocoagulation is risky while Intensive glycemic and blood pressure control procedures are hard to manage on daily bases. This review highlights the recent advancements in understanding hyperglycemia-induced biochemical and molecular alterations, systemic metabolic factors and aberrant activation of signaling cascades that ultimately lead to activation of a number of transcription factors causing functional and structural damage to retinal cells. It also reviews the established interventions and emerging molecular targets to avert diabetic retinopathy and its associated risk factors.